96.8k views
12 votes
4(v+7) = -6(3v-4) +8v


1 Answer

2 votes

Answer:

v=−27

Explanation:

Since v is on the right side of the equation, switch the sides so it is on the left side of the equation.

−6(3v−4)+8v=4(v+7)

Simplify −6(3v−4)+8v

−10v+24=4(v+7)

Simplify 4(v+7).

−10v+24=4v+28

Move all terms containing v to the left side of the equation.

−14v+24=28

Move all terms not containing v to the right side of the equation.

−14v=4

Divide each term by −14 and simplify.

v=−27

The result can be shown in multiple forms.

Exact Form:

v=−27

User Xonar
by
6.5k points